Axillary Reverse Lymphatic Mapping in the Treatment of Axillary Accessory Breast Cancer: A Case Report and Review of Management - Orli Friedman-Eldar; Siarhei Melnikau; Youley Tjendra; Eli Avisar (European Journal of Breast Health, 2022)

(untitled)
Accessory breast tissue is a rare aberration of normal breast development, that presents most commonly in the axilla. Similar to normal breast tissue, it can undergo physiologic and pathologic changes, including malignant transformation. We report a rare case of accessory breast cancer, treated with surgical resection and axillary reverse mapping (ARM), and review current literature focusing on management. We report a 68-year-old female with a history of left breast cancer treated with lumpectomy and axillary dissection, who later developed in-breast recurrence treated with re-lumpectomy and sentinel node biopsy which mapped at the contralateral (right) axilla, but was negative. Two years later screening imaging revealed right axillary tail focal asymmetry with two spiculated masses. Core biopsy showed invasive ductal carcinoma (IDC), and histologic examination of the biopsy could not determine whether this represents a new primary breast cancer or axillary metastasis from the contralateral site. She underwent lumpectomy of the two masses and sentinel node biopsy. During surgery, the masses were identified in the axilla itself, rather than the axillary tail. Final pathology revealed IDC, pT1N0(sn), and extensive ductal carcinoma in situ (DCIS). Due to positive margins, she underwent re-lumpectomy with ARM. Final pathology revealed residual DCIS with negative new margins. The patient was referred for adjuvant radiotherapy. Accessory axillary breast tissue can be confused with axillary tail tissue. It is necessary for the surgeon to distinguish between them by meticulous physical examination and radiologic evaluation, as resection of axillary breast tissue may warrant reverse lymphatic mapping for lymphedema prevention.